Dll1 Can Function as a Ligand of Notch1 and Notch2 in the Thymic Epithelium - Hirano, Ken-ichi; Hosokawa, Hiroyuki; Yahata, Takashi; Ando, Kiyoshi; Tanaka, Masayuki; Imai, Jin; Yazawa, Masaki; Ohtsuka, Masato; Negishi, Naoko; Habu, Sonoko; Sato, Takehito; Hozumi, Katsuto (Frontiers in Immunology, 2022)
T cell development in the thymus is dependent on Notch signaling induced by the interaction of Notch1, present on immigrant cells, with a Notch ligand, delta-like (Dll) 4, on the thymic epithelial cells. Phylogenetic analysis characterizing the properties of the Dll4 molecule suggests that Dll4 emerged from the common ancestor of lobe-finned and ray-finned fishes and diverged into bony fishes and terrestrial organisms, including mammals. The thymus evolved in cartilaginous fishes before Dll4, suggesting that T cell development in cartilaginous fishes is dependent on Dll1 instead of Dll4. In this study, we compared the function of both Dll molecules in the thymic epithelium using Foxn1-cre and Dll4-floxed mice with conditional transgenic alleles in which the Dll1 or Dll4 gene is transcribed after the cre-mediated excision of the stop codon. The expression of Dll1 in the thymic epithelium completely restored the defect in the Dll4-deficient condition, suggesting that Dll1 can trigger Notch signaling that is indispensable for T cell development in the thymus. Moreover, using bone marrow chimeras with Notch1- or Notch2-deficient hematopoietic cells, we showed that Dll1 is able to activate Notch signaling, which is sufficient to induce T cell development, with both the receptors, in contrast to Dll4, which works only with Notch1, in the thymic environment. These results strongly support the hypothesis that Dll1 regulates T cell development via Notch1 and/or Notch2 in the thymus of cartilaginous fishes and that Dll4 has replaced Dll1 in inducing thymic Notch signaling via Notch1 during evolution.